Melamine resin modified negative electrode material for sodium ion battery
By co-doping the melamine resin, increasing adsorption sites and introducing defects, the problem of slow diffusion kinetics of sodium ions in existing hard carbon materials is solved, and high reversible storage and excellent rate performance are achieved.
Patent Information
- Application Number
- CN202411760245.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-11-18
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-07
AI Technical Summary
The hard carbon materials prepared by existing melamine resins have slow diffusion kinetics of sodium ions in sodium ion batteries and cannot achieve high reversible storage.
By co-doping melamine resin with sulfur, the adsorption site and introduction defects are increased, and the carbon layer spacing is expanded, thereby improving the sodium storage capacity of hard carbon materials.
It realizes highly reversible storage of sodium ions, improving the cycling rate performance and reversible specific capacity of sodium ion batteries.
Smart Images

Figure CN119569030A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of preparation of negative electrode materials for sodium ion batteries, in particular to a melamine resin modified negative electrode material for sodium ion batteries. Background Art
[0002] Environmental problems caused by over-exploitation of energy and the problem of decreasing energy reserves are becoming increasingly prominent. It is imperative to develop new, clean and sustainable new energy sources. Carbon-based materials for lithium-ion batteries (LIBs) have been used for large-scale commercialization and are widely used in various electronic products and electric vehicles. However, the scarcity and high price of lithium resources have greatly limited the development of lithium-ion batteries. Sodium, which is an element in the same main group as lithium, has similar chemical properties. As a new generation solution for lithium-ion batteries, sodium-ion batteries have broad application prospects due to their low cost, excellent low-temperature performance and cycle life.
[0003] In recent years, the application research of resin-based hard carbon materials in sodium-ion batteries has been very hot. Melamine resin (MF), as an amino resin, has a unique role in certain fields due to its ultra-high nitrogen content and rich active amino groups. It is considered to be a very promising precursor. However, the hard carbon material prepared by a single melamine resin has a single microstructure, and the diffusion kinetics of sodium ions in such materials are slow, and highly reversible storage of sodium ions cannot be achieved.
[0004] Therefore, we need to further research and develop it to improve the performance of the battery and make it more widely used. Summary of the invention
[0005] The purpose of the present invention is to provide a melamine resin modified negative electrode material for sodium ion batteries in view of the problems existing in the current prior art. The material uses melamine resin as a matrix to prepare a hard carbon material. The melamine resin is used as a nitrogen source, and the pyridine nitrogen generated by the melamine resin has a strong adsorption of sodium atoms. After sulfur is doped into the melamine resin, nitrogen / sulfur co-doping is achieved. Under the synergistic effect, adsorption sites can be increased and defects can be effectively introduced, the carbon layer spacing is increased, and the sodium storage capacity of the hard carbon material is improved.
[0006] In order to achieve the above invention object, the technical solution of the present invention is as follows:
[0007] A preparation method of a melamine resin modified negative electrode material for a sodium ion battery comprises the following steps: putting melamine resin and sulfur into an agate mortar for mixed grinding; then putting the ground materials into a porcelain boat; then putting the porcelain boat into a micro-assisted tube furnace for calcining in an inert atmosphere (preferably argon); after the calcination is completed, cooling the product to room temperature; finally, grinding the product into fine particles and sieving them to obtain the melamine resin modified negative electrode material for a sodium ion battery.
[0008] Preferably, the mass ratio of melamine resin to sulfur is 3:1 to 1:3; more preferably 1:3.
[0009] Preferably, the calcination conditions are: heating to 150-180°C at a heating rate of 2-5°C / min, maintaining at 150-180°C for 1-4h, then heating to 250-350°C at a heating rate of 2-5°C / min, maintaining for 1-4h, and finally heating to 600-800°C at a heating rate of 2-5°C / min, maintaining for 1-4h.
[0010] The more preferred calcination conditions are: increase the temperature to 155°C at a heating rate of 5°C / min, and keep at 155°C for 2 hours; then increase the temperature to 280°C at a heating rate of 5°C / min, and keep at 280°C for 2 hours; finally increase the temperature to 600°C at a heating rate of 5°C / min, and keep at 600°C for 2 hours.
[0011] Furthermore, the above-mentioned method for preparing the melamine resin modified negative electrode material for sodium ion battery also includes a secondary carbonization treatment.
[0012] Preferably, before the secondary carbonization treatment, the calcined product is first mixed with an equal amount of sodium thiosulfate.
[0013] Preferably, the secondary carbonization treatment is: heating the calcined product to 250-350° C. at a heating rate of 2-5° C. / min, and maintaining the temperature for 1-4 hours.
[0014] More preferably, the secondary carbonization treatment is as follows: heating the calcined product to 350° C. at a heating rate of 2° C. / min and maintaining the temperature for 2 h.
[0015] The present application also protects a melamine resin-modified negative electrode material for a sodium ion battery prepared by the above-mentioned method or step combination.
[0016] Furthermore, the melamine resin modified negative electrode material for sodium ion batteries described above still has a reversible capacity of 189 mAh / g after 200 cycles at a current density of 1 A / g; and at a high current density of 2 A / g, the material still has a reversible capacity of 154 mAh / g after 100 cycles.
[0017] The present application also protects the use of the above-mentioned melamine resin modified negative electrode material for sodium ion batteries in negative electrode materials for sodium ion batteries.
[0018] More preferably, the present application protects the use of the above-mentioned melamine resin modified negative electrode material for sodium ion batteries in improving the capacity and rate performance of the negative electrode material of sodium ion batteries.
[0019] In the present invention, the melamine resin is modified. It is known that the atomic radius of sulfur is relatively large. Doping sulfur elements in hard carbon materials can increase adsorption sites, expand the distance between carbon layers to increase the embedding capacity of sodium ions in the carbon layers, increase the disorder of the material, and make the material produce more defects for adsorbing and storing sodium ions, so as to improve the performance of the battery.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] A hard carbon material is prepared using melamine resin as a matrix. The melamine resin is used as a nitrogen source, and the pyridine nitrogen produced has strong adsorption to sodium atoms. After the melamine resin is doped with sulfur, nitrogen / sulfur co-doping is achieved. The synergistic effect can increase the adsorption sites and effectively introduce defects, increase the carbon layer spacing, and improve the sodium storage capacity of the hard carbon material. A hard carbon material with excellent cycle rate performance and high reversible specific capacity is prepared. The hard carbon precursors used in the past have a fixed chemical composition. The present invention introduces sulfur to modify the resin to increase the storage of sodium, providing a new idea for the negative electrode material of sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The figure is a rate test diagram of the sodium ion batteries prepared in Examples 1-6 and Comparative Examples;
[0023] Figure 2 Cyclic curves of the sodium ion batteries prepared in Examples 1-6 and Comparative Examples at a discharge current density of 0.1 A / g;
[0024] Figure 3 Cyclic curves of the sodium ion batteries prepared in Example 2 and Comparative Example at a discharge current density of 1 A / g;
[0025] Figure 4 Cyclic curves of the sodium ion batteries prepared in Example 2 and Comparative Example at a discharge current density of 2 A / g. DETAILED DESCRIPTION
[0026] All features disclosed in this specification, or steps in all methods or processes disclosed, except mutually exclusive features and / or steps, can be combined in any manner.
[0027] Any feature disclosed in this specification (including claims and abstract), unless otherwise stated, may be replaced by other equivalent or alternative features having similar purposes. That is, unless otherwise stated, each feature is only an example of a series of equivalent or similar features.
[0028] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0029] The raw materials and reagents involved in this application are all commercially available products, and the devices used are commonly used devices in this field; the melamine resin is a thermosetting melamine resin; and the sulfur is sublimated sulfur.
[0030] Embodiment 1:
[0031] 3g of melamine resin and 9g of sulfur were put into an agate mortar for mixing and grinding, and then put into a porcelain boat. Under an argon environment, the temperature was first increased to 155°C at a heating rate of 5°C / min, and maintained at 155°C for 2h; then the temperature was increased to 280°C at a heating rate of 5°C / min, and maintained at 280°C for 2h; finally, the temperature was increased to 600°C at a heating rate of 5°C / min, maintained at 600°C for 2h, and cooled to room temperature to obtain melamine resin modified negative electrode material 1#.
[0032] Embodiment 2:
[0033] Put 3g of melamine resin and 9g of sulfur into an agate mortar, mix and grind them, then put them into a porcelain boat. Under argon environment, heat the temperature to 155℃ at a heating rate of 5℃ / min and keep it at 155℃ for 2h; then heat the temperature to 280℃ at a heating rate of 5℃ / min and keep it at 280℃ for 2h; finally, heat the temperature to 600℃ at a heating rate of 5℃ / min and keep it at 600℃ for 2h. After calcination, cool to room temperature.
[0034] The product that has been calcined and cooled to room temperature is then heated to 350°C at a heating rate of 2°C / min and maintained at 350°C for 2 hours to obtain melamine resin modified negative electrode material 2#.
[0035] Embodiment 3:
[0036] Put 6g of melamine resin and 6g of sulfur into an agate mortar, mix and grind them, and then put them into a porcelain boat. Under argon environment, first increase the temperature to 155℃ at a heating rate of 5℃ / min, and keep it at 155℃ for 2h; then increase the temperature to 280℃ at a heating rate of 5℃ / min, and keep it at 280℃ for 2h; finally, increase the temperature to 600℃ at a heating rate of 5℃ / min, and keep it at 600℃ for 2h to obtain melamine resin modified negative electrode material 3#.
[0037] Embodiment 4:
[0038] 9g of melamine resin and 3g of sulfur were put into an agate mortar for mixing and grinding, and then put into a porcelain boat. Under an argon environment, the temperature was first increased to 155°C at a heating rate of 5°C / min and maintained at 155°C for 2h; then the temperature was increased to 280°C at a heating rate of 5°C / min and maintained at 280°C for 2h; finally, the temperature was increased to 600°C at a heating rate of 5°C / min and maintained at 600°C for 2h to obtain melamine resin modified negative electrode material 4#.
[0039] Embodiment 5:
[0040] 3g of melamine resin and 9g of sulfur were put into an agate mortar for mixing and grinding, and then put into a porcelain boat. Under an argon environment, the temperature was first increased to 155°C at a heating rate of 5°C / min, and maintained at 155°C for 2h; then the temperature was increased to 280°C at a heating rate of 5°C / min, and maintained at 280°C for 2h; finally, the temperature was increased to 700°C at a heating rate of 5°C / min, and maintained at 700°C for 2h to obtain melamine resin modified negative electrode material 5#.
[0041] Embodiment 6:
[0042] 3g of melamine resin and 9g of sulfur were put into an agate mortar for mixing and grinding, and then put into a porcelain boat. Under an argon environment, the temperature was increased to 155°C at a heating rate of 5°C / min, maintained at 155°C for 2h, then increased to 280°C at a heating rate of 5°C / min, maintained for 2h, and finally increased to 800°C at a heating rate of 5°C / min, maintained for 2h, to obtain melamine resin modified negative electrode material 6#.
[0043] Comparative Example 1 (Comparative Example):
[0044] Put 12g of melamine resin into an agate mortar for mixing and grinding, then put it into a porcelain boat. Under argon environment, first increase the temperature to 155℃ at a heating rate of 5℃ / min, and keep it at 155℃ for 2h; then increase the temperature to 280℃ at a heating rate of 5℃ / min, and keep it at 280℃ for 2h; finally, increase the temperature to 600℃ at a heating rate of 5℃ / min, and keep it at 600℃ for 2h to obtain material 7#.
[0045] The electrochemical properties of the sodium ion battery negative electrode materials prepared in Examples 1-6 and the material obtained in Comparative Example 1 at different discharge current densities are compared. The specific results are shown in Table 1.
[0046] Table 1: Comparison of the performance of the negative electrodes of sodium ion batteries prepared in different embodiments and comparative examples
[0047]
[0048] From the above table and Figure 1It can be seen that the sodium ion battery prepared in Example 2 has a discharge specific capacity of 311 mAh / g, 263 mAh / g, 189 mAh / g, 154 mAh / g, and 121 mAh / g at current densities of 50 mA / g, 100 mA / g, 500 mA / g, 1 A / g, and 2 A / g, respectively, which are higher than the sodium ion batteries prepared in other embodiments and comparative examples. In the present invention, the melamine resin modified negative electrode material obtained by sulfur doping and secondary carbonization has a high reversible specific capacity and excellent rate performance in the negative electrode of the sodium ion battery. It shows that the mass ratio of melamine resin and sulfur, the calcination temperature, and the secondary carbonization have a great influence on the rate of the sodium ion battery of the melamine resin modified negative electrode material. Preferably, the mass ratio of melamine resin and sulfur is 1:3, and the composite hard carbon negative electrode prepared at 600°C by secondary carbonization has the best performance.
[0049] Figure 2 The cycle curves of the sodium ion batteries prepared in Examples 1-6 and Comparative Examples at a discharge current density of 0.1 A / g. Figure 2 It can be seen that the capacity decay of the sodium ion battery prepared in Example 2 is relatively serious in the first few cycles, which may be related to the internal activation of the battery; in the subsequent cycles, the capacity decay is very slow, and there is still a discharge capacity of 255 mAh / g after 100 cycles.
[0050] Furthermore, Figure 3 and Figure 4 The cycle curves of the sodium ion batteries prepared in Example 2 and the comparative example at discharge current densities of 1A / g and 2A / g respectively. The sodium ion battery prepared in Example 2 still has a reversible capacity of 189mAh / g after 200 cycles at a current density of 1A / g; at a high current density of 2A / g, the material still has a reversible capacity of 154mAh / g after 100 cycles. It can be seen that the prepared melamine resin modified negative electrode material can still maintain a high discharge specific capacity and good cycle stability at a large discharge current density, showing excellent rate performance.
[0051] In summary, the melamine resin modified negative electrode material prepared by the present invention, when used as a negative electrode material for a sodium ion battery, has improved discharge specific capacity and rate performance, and can be used for a high-performance sodium ion battery negative electrode. The emergence of sodium ion batteries not only alleviates the problem of limited lithium ion resources and high costs, but also has simple positive and negative electrode materials, cheap and easy to obtain, environmentally friendly, safe, simple production process and low cost. It is a sodium ion battery with high specific capacity, high cycle performance and high safety.
[0052] The above-mentioned embodiments only express the specific implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the protection scope of the present application. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the technical solution concept of the present application, and these all belong to the protection scope of the present application.
[0053] This background section is provided to generally present the context of the invention, and the work of the presently named inventors, the work to the extent described in this background section, and aspects of this section that did not constitute prior art at the time of application are neither explicitly nor implicitly admitted to be prior art to the present invention.
Claims
1. A method for preparing a melamine resin modified negative electrode material for a sodium ion battery, characterized in that The method comprises the following steps: putting melamine resin and sulfur into an agate mortar for mixed grinding; then putting the ground substances into a porcelain boat; then putting the porcelain boat into a micro-assisted tube furnace for calcination in an inert gas environment; after the calcination is completed, the product is cooled to room temperature; finally, the product is ground into fine particles and then sieved to obtain a melamine resin-modified negative electrode material for a sodium ion battery.
2. The method for preparing a melamine resin modified negative electrode material for a sodium ion battery according to claim 1, characterized in that: The mass ratio of melamine resin to sulfur is 3:1 to 1:
3.
3. The method for preparing a melamine resin modified negative electrode material for a sodium ion battery according to claim 1 or 2, characterized in that: The inert gas is argon.
4. The method for preparing a melamine resin modified negative electrode material for a sodium ion battery according to claim 3, characterized in that: The calcination conditions are as follows: increase the temperature to 150-180°C at a heating rate of 2-5°C / min, and keep at this temperature for 1-4 hours; then increase the temperature to 250-350°C at a heating rate of 2-5°C / min, and keep at this temperature for 1-4 hours; finally increase the temperature to 600-800°C at a heating rate of 2-5°C / min, and keep at this temperature for 1-4 hours.
5. The method for preparing a melamine resin modified negative electrode material for a sodium ion battery according to claim 1, 2 or 4, characterized in that The method also includes a secondary carbonization treatment; before the secondary carbonization treatment, the calcined product is first mixed with an equal amount of sodium thiosulfate.
6. The method for preparing a melamine resin modified negative electrode material for a sodium ion battery according to claim 5, characterized in that: The secondary carbonization treatment is as follows: the calcined product is heated to 250-350°C at a heating rate of 2-5°C / min and maintained at this temperature for 1-4h.
7. A melamine resin modified negative electrode material for a sodium ion battery prepared according to the method of claim 1, 2, 4 or 6.
8. The melamine resin modified negative electrode material for sodium ion battery according to claim 7, characterized in that: At a current density of 1A / g, the material still has a reversible capacity of 189mAh / g after 200 cycles; at a high current density of 2A / g, the material still has a reversible capacity of 154mAh / g after 100 cycles.
9. Use of the melamine resin modified negative electrode material for sodium ion battery according to claim 7 in negative electrode materials of sodium ion battery.
10. Use of the melamine resin modified negative electrode material for sodium ion battery according to claim 7 in improving the capacity and rate performance of the negative electrode material of the sodium ion battery.